Vitamin D status and its influence on outcomes following major burn injury and critical illness - Al-Tarrah, Khaled (Burns Trauma, 2018)
Vitamin D deficiency is common among the general population. It is also observed in up to 76% of critically ill patients. Despite the high prevalence of hypovitaminosis D in critical illness, vitamin D is often overlooked by medical staff as the clinical implications and consequences of vitamin D deficiency in acute contexts remain to be fully understood. Vitamin D has a broad range of pleotropic effects on various processes and systems including the immune-inflammatory response. 1α,25-dihydroxyvitamin D (1,25(OH)(2)D), has been shown to promote a tolerogenic immune response limiting deleterious inflammatory effects, modulation of the innate immune system, and enhancement of anti-microbial peptides. Vitamin D deficiency is frequently observed in critically ill patients and has been related to extrinsic causes (i.e., limited sunlight exposure), magnitude of injury/illness, or the treatment started by medical doctors including fluid resuscitation. Low levels of vitamin D in critically ill patients have been associated with sepsis, organ failure, and mortality. Despite this, there are subpopulations of critical illness, such as burn patients, where the literature regarding vitamin D status and its influence on outcomes remain insufficient. Thermal injury results in damage to both burned and non-burned tissues, as well as induces an exaggerated and persistent immune-inflammatory and hypermetabolic response. In this review, we propose potential mechanisms in which burn injury affects the vitamin D status and summarizes current literature investigating the influence of vitamin D status on outcomes. In addition, we reviewed the literature and trials investigating vitamin D supplementation in critically ill patients and discuss the therapeutic potential of vitamin D supplementation in burn and critically ill patients. We also highlight current limitations of studies that have investigated vitamin D status and supplementation in critical illness. Thermal injury influences vitamin D status. More studies investigating vitamin D depletion in burn patients and its influence on prognosis, via standardized methodology, are required to reach definitive conclusions and influence clinical practice.